Pengetahuan Masyarakat Umum dan Masyarakat Santri Terhadap Bank Syariah : Studi Kasus Kemukiman Bandar Baru Kecamatan Banda Baro Kabupaten Aceh Utara - Muhammad Nasir; Mukhlis Mukhlis; Miskarina Miskarina (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2016)
Islamic Banking is a bank that runs its main activity to gather funds from community and to funneling funds to community based on the principles of Shariah. This study discusse about the knowledge of the general public and the islamic students toward Islamic banking.The purpose of this research is to find out how the knowledge of the general public and the islamic students toward Islamic banking. The objects of this research are community general public and Islamic student in Kemukiman Bandar Baru. For the general public is composed of five villages, are: Cot Jabet, Ulee Nyeue, Paya Uleue, Alue Keurinyai and Jamuan. For Islamic Students consists of Integrated Dayah Darul Ma’rifah and Recitation Hall Babussalam Al-Aziziyah. The Data used in this research is the primary data obtained through interviews of respondents directly by using the questionnaire. In the sample, methods used is probability sampling and to define samples in research is used technique stratified sampling and engineering clusters of sampling.Hence, samples are obtained for the general public and islamic students for each are 100 respondents.Test statistics instrument used for analysis this research is test different samples average two pairs (paired sampels test). Test result average difference suggests that there is a difference of knowledge among the general public and the islamic students of Islamic banking. This suggests that the knowledge society students are still less aware of Islamic banking. The implication may provide opportunities to the existing Islamic banking in the community to conduct socialization to society, particularly the Islamic students.Keywords: General Public, Islamic students, Islamic Banking